Carrier as a subject of contractual obligations to provide transport services - Lukasevych-Krutnyk, Iryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article is devoted to the study of the concept of carrier as a subject of contractual obligations for the provision of transport services. Its relevance is due to the fact that, taking into account the European integration vector of our state, the legislation of Ukraine, including in the field of contractual regulation of transport services, must go the way of maximum approximation to European standards. In this context, reference should be made to the Interinstitutional Agreement between the European Parliament, the Council of the EU and the EU Commission on general guidelines for quality assurance in the design of Community legislation of 22 December 1998 (1999 / C 73/01), the preamble to which states that clear, simple and clear drafting of legislation by the members of the Community is necessary, as such acts must be transparent and understandable to the public and participants in economic relations; concepts or terminology specific to any national legal system should be used with caution. It is important that the terminology is stable, uniform both within such an act and in the whole array of existing acts, in particular those relating to one area of regulation. Identical concepts should be expressed in the same terms as far as possible, without deviating from their meaning in ordinary, legal or technical language. Given this, the analysis through the prism of the established requirements of the conceptual apparatus, which is used in the legislation of Ukraine in the regulation of contractual relations for the provision of transport services. The purpose of the study is to formulate the concept and define the legal requirements for the carrier as a subject of contractual obligations to provide transport services in accordance with international and national law of Ukraine, distinguishing the concept of carrier with other closest concepts. The concept of carrier in international regulations and legislation of Ukraine is clarified and legal definitions are classified into two groups: 1) in the content of which attention is focused on the object of transportation; 2) in the content of which the object of transportation and the type of transport are indicated. Based on the analysis of special features inherent exclusively to the carrier, the model concept of the carrier is proposed: “The carrier is a natural or legal person who has entered into a contract of carriage, owns or otherwise legally owns vehicles and this type of transportation requires its receipt". The main requirements to the carrier as a subject of contractual obligations for the provision of transport services are formulated: 1) it is a party to the contract of carriage, which undertakes to provide transport services on a paid contractual basis; 2) it is a person who on the basis of ownership or other legal grounds owns a vehicle and carries out its operation; 3) obtaining a license, if the implementation of this type of transportation requires its receipt. The concepts of "national carrier", "actual carrier", "consecutive carrier", "substitute carrier" are distinguished. The content of the terms "actual carrier" and "substitute carrier" has been found to be identical. The introduction of the concept of the actual carrier is associated with the definition of the liability of the carrier as a party to the contract. In cases where all or part of the carriage is entrusted to the actual carrier, the carrier under the contract remains responsible for all carriage. It is argued that the carrier may transfer the performance of the contract of carriage to the actual carrier only in cases where this is established in the content of the contract of carriage. The successive carrier, in contrast to the actual carrier, is a party to the contract of carriage and, as a rule, is responsible for the part of the carriage that he performed.